2006
DOI: 10.1016/j.jvs.2005.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Decreased wall shear stress in the common carotid artery of patients with peripheral arterial disease or abdominal aortic aneurysm: Relation to blood rheology, vascular risk factors, and intima-media thickness

Abstract: This is the first report, to our knowledge, showing that wall shear stress of the common carotid artery is decreased in patients with symptomatic PAD and in patients with AAA. Rheologic variables are less important in predicting wall shear stress than age, triglycerides, and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
3
24
1
1
Order By: Relevance
“…Plasma viscosity was determined in ethylenediaminetetraacetic acid plasma by using a viscometer of the capillary type at 25 °C (Processer Viscosity System 1, Lauda, Germany). Whole blood viscosity was measured in ethylenediaminetetraacetic acid plasma using a rotational viscometer (Contraves LS 30, Contraves, Switzerland) at a high shear rate (94.5/s) at 37 °C (13). Peak and mean wall shear stress (dyn/cm 2 ) were calculated as previously described (13): shear stress = 4 × blood viscosity (P) × blood velocity (cm/s)/internal diameter of the main pulmonary artery (cm).…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…Plasma viscosity was determined in ethylenediaminetetraacetic acid plasma by using a viscometer of the capillary type at 25 °C (Processer Viscosity System 1, Lauda, Germany). Whole blood viscosity was measured in ethylenediaminetetraacetic acid plasma using a rotational viscometer (Contraves LS 30, Contraves, Switzerland) at a high shear rate (94.5/s) at 37 °C (13). Peak and mean wall shear stress (dyn/cm 2 ) were calculated as previously described (13): shear stress = 4 × blood viscosity (P) × blood velocity (cm/s)/internal diameter of the main pulmonary artery (cm).…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…One study reported that CIMT values in patients with AAA and PAD increased at a similar rate to those of healthy volunteers (29). Studies maintaining the opposite, however, have reported similar CIMT values in patients with AAA to those in healthy volunteers but significantly lower values than those in patients with PAD (10,30).…”
Section: Discussionmentioning
confidence: 98%
“…WSS is associated with traditional risk factors, but only smoking, age and triglycerides remained significantly associated with this on multivariate analysis (146). An inverse relationship exists between WSS and carotid wall thickness has been reported (147).…”
Section: Wall Shear Stress (Wss)mentioning
confidence: 91%